Marfan Syndrome and Pregnancy-A Case Report and Review of the Literature - Özyüncü, Özgür; Esin, Sertaç; Gyimadu, Adam (Gynecology Obstetrics & Reproductive Medicine, 2010)
Marfan syndrome is an autosomal dominant disorder characterized by abnormalities of skeletal, cardiovascular and ocular systems. Pregnant women may suffer from hemodynamic stress resulting from increased cardiac output and structural changes in the aortic wall leading dilatation and dissection of the aorta. It is usually advised to avoid pregnancy to women with Marfan Syndrome however with advances in medicine, successful pregnancies with Marfan Syndrome are reported. Therefore, the aim of this study is to review the literature over a case with a successful management during pregnancy.